Communication and performance: Banking employee perspective - Nasri Ashari; Syamsul Ridjal; Akhmad Muhammadin (Jurnal Inovasi Ekonomi, 2021)
The purpose of this study is to investigate the effect of organizational communication on employee performance mediated by organizational commitment and moderated by motivation at PT. Bank Sulawesi Selatan (Sulselbar). The research sample uses 100 employees and uses path analysis. This study shows that organizational communication encourages employee performance, and communication mediated by commitment shows a higher impact on performance. The performance will also get better when moderated by motivation.